The Essentiality of Sustainable Arechitecture Design of Medical Centers with the Physical Therapy Approach - Aynaz Khoshsokhan; Lida Balilan Asl (Budapest International Research and Critics University, 2023)
The aim of this study was to assess the essentiality of sustainable architecture design of medical centers with the physical therapy approach. Using library resources, this study was attempted to descriptively-analytically evaluate the role of sustainability components on the environmental quality of physical therapy centers. The physical therapy centers, not only need to meet the requirements of their users in terms of functionality, but also need to use sustainable architectural components such as proper location, use of clean and renewable energy, selection of appropriate materials, management of pollution and water resources in reducing the consumption of non-renewable energy, reducing the production of pollution and waste and losses to reduce environmental degradation. Due to the sensitivity of the patients and the direct impact of designed environment on their recovery, following the principles of sustainability and providing design solutions tailored to the environmental needs of physical therapy centers, including connection with nature, use of antibacterial materials, pollution and waste management, and attention to water supply sources, can promote the process of patients' mental and physical health. It can be concluded that attention to sustainable architectural components should be considered not only as a suggestion but also as a requirement in the design of medical centers.